BIOETHANOL FROM CHEESE WASTE (WHEY) USING KLUYVEROMYCES MARXIANUS - Alif Nur Laili Rachmah; Ratri Sekaringgalih; Binti Ruliana; Ansori Ansori (Jurnal Inovasi Pendidikan dan Sains, 2023)
Alternatives to petroleum scarcity are of much concern to researchers. The development of bioethanol is one of the renewable energies that must be supported by research from various sources of raw materials so that it can be converted into bioethanol. Generally, the raw material of bioethanol used contains sugar and starch. if biomass used sugar cane and cassava then the availability of food will also be threatened. Therefore one of the alternative raw materials that can be used is industrial waste cheese (whey). Whey is the side of the product cheese industry, which contains 4-5%. The aim of the study is to optimate whey fermentation to the production of bioethanol using Kluyveromyces marxianus with the variation of time and starter volume. Bioethanol production with raw material lactose which is contained in whey used Kluyveromyces Marxianus with variabel changed time fermentation and starter volume. For time fermentation variables are 24, 48, 60, 72 dan 84 hours, and for volume starter variabel are 20%, 22%, dan 24% v/v. The highest content of bioethanol production used Kluyveromyces Marxianus on variable starter volume 24% at time 84 hours was obtained 0,32% bioethanol content with pH 3,5